Pendampingan Program Kebersihan Lingkungan pada Perumahan Organda, Padang Bulan Kota Jayapura - Hosio, Yakomina Flora; Yoseb, Boari; Samori, Yosina; Mikir, Agustinus Wahyu (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This service activity aims to motivate the community to clean up environment at Organda Housing, and to give understandings how importance keeping the environment clean in order to create a comfortable, clean and safe environment. The methods or stages in implementing this community service are the preparation stage, the implementation stage and the evaluation stage. The results of the Community Service activities that have been carried out, it can be concluded that the process of education and environmental cleaning at Organda Housing, from the beginning to the final stage is evidenced by the very good response from the community by following the directions given. In addition, an environmental clean-up has been carried out by a team of students at the Ottow Geissler University in Papua, who are assisted by youths and the community.